Interaction of Climate Change and Anthropogenic Activity on the Spatiotemporal Changes of Surface Water Area in Horqin Sandy Land, China - Xueping Chen; Xueyong Zhao; Yanming Zhao; Ruixiong Wang; Jiannan Lu; Haiyan Zhuang; Liya Bai (Remote Sensing, 2023)
Surface water dynamics are sensitive to climate change and anthropogenic activity, and they exert important feedback to the above two processes. However, it is unclear how climate and human activity affect surface water variation, especially in semi-arid regions, such as Horqin Sandy Land (HQSL), a typical part of the fragile region for intensive interaction of climate and land use change in northern China. We investigated the changes of spatiotemporal distribution and the influence of climatic and anthropogenic factors on Surface Water Area (SWA) in HQSL. There are 5933 Landsat images used in this research, which were processed on the Google Earth Engine cloud platform to extract water bodies by vegetation index and water index method. The results revealed that the area and number of water bodies showed a significant decrease in HQSL from 1985 to 2020. Spatially, the SWA experienced different amplitudes of variation in the Animal Husbandry Dominated Region (AHDR) and in the Agriculture Dominated Region (ADR) during two periods; many water bodies even dried up and disappeared in HQSL. Hierarchical partitioning analysis showed that the SWA of both regions was primarily influenced by climatic factors during the pre-change period (1985–2000; the mutation occurred in 2000), and human activity has become more and more significantly important during the post-change period (2001–2020). Thus, it is predictable that SWA variation in the following decades will be influenced by the interaction of climate change and human activity, even more by the later in HQSL, and the social sectors have to improve their ability to adapt to climate change by modifying land use strategy and techniques toward the sustainable development of water resources.